Sovereign Bond Holdings under Bank Competition in Vietnam - Japan Huynh (Asian Academy of Management Journal of Accounting and Finance, 2024)
This article investigates the impact of bank competition on the holdings of sovereign bonds. Using bank-level data from Vietnam for 2007–2021, we design various proxies to indicate bank competition and apply the system generalized method of moments (GMM) to conduct main regressions. We find that banks are more likely to hold domestic treasury securities in response to greater market competition. We add strength to our analysis by conducting subsample checks to allow for potential structural breaks due to the financial and COVID-19 pandemic crises. In addition, we find that sovereign debt holdings are less prominent when banks are more inclined to search for higher income during periods of intense competition. Meanwhile, the risk profile of the financial institution does not modify the potency of the market competition-bond holding association. These results suggest that banks would retain more sovereign debt under competitive pressure for strategic rather than precautionary motives.